CHANGES IN LABOR MARKET INDICATORS IN A PANDEMIC - Vositjon Imomov (International Scientific and Current Research Conferences, 2021)
This article analyzes the state of the labor market and examines changes in its indicators in a pandemic. It clearly outlines the processes that affect labor market indicators, the systemic problems that arise in this regard, and the factors that lead to them. The Government has also detailed the measures that need to be taken during the pandemic and in the context of rising unemployment in the labor market. As a result of the analysis, well-founded proposals were put forward to address the identified problems, reduce unemployment and increase employment.